Towards robust monocular depth estimation: a new baseline and benchmark - Xian, Ke (2024)
Before deploying a monocular depth estimation (MDE) model in real-world applications such as autonomous driving, it is critical to understand its generalization and robustness. Although the generalization of MDE models has been thoroughly studied, the robustness of the models has been overlooked in previous research. Existing state-of-the-art methods exhibit strong generalization to clean, unseen scenes. Such methods, however, appear to degrade when the test image is perturbed. This is likely because the prior arts typically use the primary 2D data augmentations (e.g., random horizontal flipping, random cropping, and color jittering), ignoring other common image degradation or corruptions. To mitigate this issue, we delve deeper into data augmentation and propose utilizing strong data augmentation techniques for robust depth estimation. In particular, we introduce 3D-aware defocus blur in addition to seven 2D data augmentations. We evaluate the generalization of our model on six clean RGB-D datasets that were not seen during training. To evaluate the robustness of MDE models, we create a benchmark by applying 15 common corruptions to the clean images from IBIMS, NYUDv2, KITTI, ETH3D, DIODE, and TUM. On this benchmark, we systematically study the robustness of our method and 9 representative MDE models. The experimental results demonstrate that our model exhibits better generalization and robustness than the previous methods. Specifically, we provide valuable insights about the choices of data augmentation strategies and network architectures, which would be useful for future research in robust monocular depth estimation. Our code, model, and benchmark can be available at https://github.com/KexianHust/Robust-MonoDepth .